1998
DOI: 10.2307/3284632
|View full text |Cite
|
Sign up to set email alerts
|

Description of a New Neospora Species (Protozoa: Apicomplexa: Sarcocystidae)

Abstract: Neospora hughesi n. sp. was isolated from the central nervous system tissue of an adult equine (Equus caballus) from California. The tachyzoites are crescent-shaped, approximately 2 x 5 microm (1.8-3.0 x 4.0-7.0 microm), with characteristic apical complex structures consisting of an anterior polar ring, conoid, numerous rhoptries filled with a uniform electron-dense material, and 22 microtubules extending posteriorly from the polar ring. Comparison of N. hughesi to canine and bovine Neospora caninum isolates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0
24

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 38 publications
2
76
0
24
Order By: Relevance
“…However, two sero-epidemiological surveys performed in North America using the N. caninum Agglutination Test (NAT) or IFAT have demonstrated that 11.5 and 23.3% of horse sera regarded as positive respectively 160 F. De Meerschman et al [8,17]. Recently, N. hughesi was identified in the horse in California [31]. Since N. caninum cross reacts serologically with this new species [31], seroconversion is indicative of exposure to either of these two parasites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two sero-epidemiological surveys performed in North America using the N. caninum Agglutination Test (NAT) or IFAT have demonstrated that 11.5 and 23.3% of horse sera regarded as positive respectively 160 F. De Meerschman et al [8,17]. Recently, N. hughesi was identified in the horse in California [31]. Since N. caninum cross reacts serologically with this new species [31], seroconversion is indicative of exposure to either of these two parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, N. hughesi was identified in the horse in California [31]. Since N. caninum cross reacts serologically with this new species [31], seroconversion is indicative of exposure to either of these two parasites. The use of horse serum could, therefore, also lead to unexpectedly high background values when performing IFAT or ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…caninum was firstly described in dogs in Norway (Bjerkas et al, 1984), from there on, it has been described in many warm-blooded species (Dubey and Lindsay, 1996). N. hughesi has been reported for the first time by Marsh et al (1998) who isolated a protozoan very similar to N. caninum (however, with structural and molecular differences) from brain and spinal marrow of a horse that was showing signs compatible with equine protozoal myeloencephalitis (EPM).The biological cycle of N. caninum was described by McAllister et al (1998) and involves definitive (DH) and intermediate (IH) hosts. The definitive ones are dogs and coyotes (McAllister et al, 1998;Gondim et al, 2004) and, besides sheltering the agent, they are Recebido em 16 de outubro de 2010 Aceito em 25 de fevereiro de 2011 E-mail: gugatoscan@hotmail.com characterized by excreting oocysts in their feces.…”
mentioning
confidence: 99%
“…N. hughesi has been reported for the first time by Marsh et al (1998) who isolated a protozoan very similar to N. caninum (however, with structural and molecular differences) from brain and spinal marrow of a horse that was showing signs compatible with equine protozoal myeloencephalitis (EPM).…”
mentioning
confidence: 99%
See 1 more Smart Citation